Premature infants have impaired airway antiviral IFNγ responses to human metapneumovirus compared to respiratory syncytial virus (2015)
Background: It is unknown why human metapneumovirus (HMPV) and respiratory syncytial virus (RSV) cause severe respiratory infection in children, particularly in premature infants. Our aim was to investigate if there are defective airway antiviral responses to these viruses in young children with history of prematurity. Methods: Nasal airway secretions were collected from 140 children ≤3 y old without detectable virus (n = 80) or with PCR-confirmed HMPV or RSV infection (n = 60). Nasal protein levels of IFNγ, CCL5/RANTES, IL-10, IL-4, and IL-17 were determined using a multiplex magnetic bead immunoassay. Results: Full-term children with HMPV and RSV infection had increased levels of nasal airway IFNγ, CCL5, and IL-10 along with an elevation in Th1 (IFNγ)/Th2 (IL-4) ratios, which is expected during antiviral responses. In contrast, HMPV-infected premature children (< 32 wk gestation) did not exhibit increased Th1/Th2 ratios or elevated nasal airway secretion of IFNγ, CCL5, and IL-10 relative to uninfected controls. Conclusion: Our study is the first to demonstrate that premature infants have defective IFNγ, CCL5/RANTES, and IL-10 airway responses during HMPV infection and provides novel insights about the potential reason why HMPV causes severe respiratory disease in children with history of prematurity.